Knowing More Than We Can Tell: People Are Aware of Their Biased Self-Perceptions. (July 2015) - Bollich, Kathryn L.; Rogers, Katherine H.; Vazire, Simine
There is no question that biases exist in self-perceptions of personality. To what extent do people have insight into their positive and negative self-biases? In two samples (total N = 130), people with positive biases (i.e., self-perceptions that are more positive than a reputation-based criterion measure) accurately described themselves as positively biased, and people with negative biases accurately described themselves as negatively biased. Furthermore, people were able to distinguish which traits they were more or less biased about. These findings suggest that people may know more about themselves than they initially admit. Implications for the use of self-reports and the study of self-knowledge are discussed.